Design of a highly miniaturized novel electromagnetic bandgap (EBG) material for performance improvement in microwave components. Issue 1 (February 2021) - Mohan, C; Esther Florence, S; Vimal Samsingh, R; Ahmed, Naveed
Abstract: In this paper, a new uniplanar compact spiral-shaped asymmetric electromagnetic bandgap structure for a low-profile antenna is proposed. The proposed EBG design is constructed, with four spiral-shaped radiators are combined with centre element, which printed on an FR-4 dielectric material. The miniaturisation of the EBG unitcell has been achieved by increasing the electrical length of the radiating element. The overall dimensions of the proposed EBG structure is very low about only 0.03 λ0 × 0.03 λ0 (λ0 is the free space wavelength at the resonating frequency of 2.4 GHz). Miniaturization of the proposed EBG structure is 86 % obtained when compared to conventional EBG structure for 2.4 GHz. This spiral-shaped EBG design can adequately suppress surface wave and it exhibits effective band-stop response at resonant frequency 2.4 GHz. The proposed EBG structure also provides improved performance especially peak gain, when it is placed beneath the antenna. A significant improvement in peak gain up to 1.7 dB and 15 % bandwidth at resonant frequency 2.4 GHz has been achieved after integration with proposed EBG design.